GC-MS Analysis and Gastroprotective Evaluations of Crude Extracts, Isolated Saponins, and Essential Oil from Polygonum hydropiper L. - Ayaz, Muhammad; Junaid, Muhammad; Ullah, Farhat; Sadiq, Abdul; Shahid, Muhammad; Ahmad, Waqar; Ullah, Ihsan; Ahmad, Ashfaq; Syed, Nawazish-i-Husain (Frontiers in Chemistry, 2017)
Peptic ulceration is among the most prevalent gastrointestinal disorders characterized by pepsin and gastric acid mediated mucosal damage, as result of imbalance between defensive and offensive processes. The main objective of the current study was to investigate the antiulcer potentials of Polygonum hydropiper crude methanolic ectract (Ph.Cr) in aspirin induced ulcerogenesis using pylorus ligated rat model. In-vitro urease and Proteus mirabilis inhibitory potentials were evaluated using standard protocols. All fractions were analyzed using GC-MS to identify major components. The aspirin induced ulcerogenesis in pylorus ligated rat model was associated with significant changes in the mean ulcer score (F5,30 = 7.141, P = 0.0002), gastric juice volume (F5,30 = 8.245, P < 0.0001), gastric juice pH (F5,30 = 5.715, P = 0.0008), free acidity (F5,30 = 4.544, P = 0.0033), total acidity (F5,30 = 2.740, P = 0.0373) and pepsin concentration (F5,30 = 2.335, P = 0.0664). Pre treatment with Ph.Cr at 100, 200 and 400 mg/kg dose exhibited marked gastroprotective and anti-ulcerogenic effect in the aspirin induced pyloric ligation ulcerogenesis model at 100, 200 and 400 mg/kg as indicated by ulcerative biochemical parameters. In urease inhibition assay, leaves essential oil (Ph.Lo), saponins (Ph.Sp) and chloroform extract (Ph.Chf) exhibited highest activities with IC50 of 90, 98 and 520 µg/ml respectively. Ph.Sp, Ph.Chf, ethyl acetate (Ph.EtAc) and Ph.Cr showed MICs of 25, 30, 32.25 and 40.50 µg/ml respectively against Proteus mirabilis. Several compounds were identified in GC-MS analysis of samples. Significant in-vivo antiulcer, urease inhibitory as well as anti-proteus potentials of P. hydropiper solvent extracts, signify its potential use for the management of peptic ulcers and may provide scientific bases for the traditional uses of the plant.